New data on taxonomy of recent Prophalangopsidae (Orthoptera: Hagloidea) - Liu, Xianwei; Zhou, Min; Bi, Wenxuan; Tang, Liang (Zootaxa, 2009)
Keys to subfamilies, genera and species of the Prophalangopsidae are provided. Two new species Aboiloilomimus guizhouensis sp. n. and Aboiloimimus ornatus sp. n. are described respectively from Guizhou and Sichuan of China. The female of Prophalangopsis obscura is found for the first time from Tibet and is given a diagnosis. All type specimens examined in this study are deposited in Shanghai Entomological Museum, CAS.